2021
DOI: 10.1111/and.14198
|View full text |Cite
|
Sign up to set email alerts
|

Xuefu Zhuyu decoction improves asthma‐induced asthenozoospermia based on network pharmacology and in vivo experiment

Abstract: Asthma is a heterogeneous disease, composed of different phenotypes, which are driven by different mechanisms and pathways.The global prevalence of asthma ranges from 1% to 18%, and it is estimated that there are about 300 million asthma patients in the world (Eder et al., 2006). In individuals with severe asthma, the activation of apoptotic pathways caused by hypoxia and severe reactions has attracted widespread attention. At the same time, in the world, 8%-12% of couples of childbearing age are affected by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In recent years, there has been an increasing number of clinical studies on TCM , 76 , 77 , 78 and randomized controlled trials 79 , 80 , 81 have also been carried out one after another, which achieved certain effects and were increasingly recognized by Western Medicine. Therefore, the TCM decoction plays an important role in improving the number of sperm.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been an increasing number of clinical studies on TCM , 76 , 77 , 78 and randomized controlled trials 79 , 80 , 81 have also been carried out one after another, which achieved certain effects and were increasingly recognized by Western Medicine. Therefore, the TCM decoction plays an important role in improving the number of sperm.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding on the association between asthma and abnormal spermatozoa risk is consistent with previous studies. Recently, Multiple mouse model studies consistently indicate an association between asthma and spermatozoa quality, primarily characterized by significantly lower spermatozoa concentration and motility in the asthma mouse group compared to the control group ( Xu et al, 2016 ; Deng et al, 2021 ; Wang et al, 2021 ; Feng et al, 2022 ). Xu et al (2016) propose that asthma could activate the mitochondrial apoptosis signaling pathway in the mouse testis, thereby impacting spermatozoa quality.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Feng et al (2022) argue that asthma can modulate the HIF-1 signaling pathway, resulting in increased expression of IL6, Stat3, HIF-1α protein, and mRNA, ultimately leading to spermatozoa apoptosis. Additionally, Deng et al (2021) suggest that asthma can induce the production of abnormal spermatozoa by upregulating the expression of IL-6, vascular endothelial growth factor A, and mRNA while inhibiting albumin expression levels. In addition, only one cross-sectional study in humans found a potential association between self-reported asthma patients and reduced testicular function, primarily manifested by decreased spermatozoa concentration and total spermatozoa count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation